1997
DOI: 10.1007/s000110050169
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A 3 receptors promote degranulation of rat mast cells both in vitro and in vivo

Abstract: These results indicate that stimulation of adenosine A3 receptors both enhances degranulation in vitro and directly produces degranulation of rat mast cells in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 14 publications
6
52
0
Order By: Relevance
“…Our studies show that plasma protein extravasation in response to adenosine is mediated entirely through activation of the A 3 receptor, as adenosine cannot provoke this physiological response in mice lacking this receptor. These findings are consistent with reports showing that pharmacologic reagents that preferentially bind to the A 3 receptor are effective at inducing edema formation (30,38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our studies show that plasma protein extravasation in response to adenosine is mediated entirely through activation of the A 3 receptor, as adenosine cannot provoke this physiological response in mice lacking this receptor. These findings are consistent with reports showing that pharmacologic reagents that preferentially bind to the A 3 receptor are effective at inducing edema formation (30,38).…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, most studies suggest that A 2B and A 3 receptors are predominantly involved (24)(25)(26)(27)(28)(29)(30)(31)(32). The differential importance assigned to these receptors in mast-cell degranulation may reflect the fact that mast cells examined were from different species and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This effect of adenosine on preformed mediator release is mediated by A 3 adenosine receptors in rodents (23,(41)(42)(43), but perhaps not in human (44) or canine (45) mast cells. We found that an enhanced Ag-induced degranulation in A 2B KO BMMCs was observed both in the absence and presence of the adenosine receptor agonist NECA, but the degree of potentiation mediated via A 3 receptors was essentially the same as in WT cells.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, our results provide unequivocal evidence for a role of the A3R in mediating signaling provoked in HMCs undergoing inflammatory processes. Notably, although studies in rodent mast cells and rodent animal models have firmly established the central role played by the A3R in mediating inflammatory processes, including bronchoconstriction, hypotension, and cutaneous allergic reactions (23)(24)(25)(26), the role of the A3R in humans remained controversial. The literature split between reports revealing proinflammatory functions of the A3R, as opposed to evidence demonstrating anti-inflammatory and protective outcomes have led Gessi et al to coin the A3R as the "Dr. Jekyll and Mr. Hyde" of the inflammatory reaction (27).…”
Section: Discussionmentioning
confidence: 99%